Follicolous fungi occurring at Biratnagar, Nepal - Bhagat, I. M. (Nepalese Journal of Biosciences, 2014)
There are different types of vegetables cultivated in different seasons. Vegetables are attacked by different types of pathogens such as fungi, viruses, nematodes and bacteria. Out of all these pathogens the fungi play an important role in mass destruction of vegetables. They reduce the quality and quantity of vegetable production. There are different kinds of diseases caused by fungi in vegetables and most commonly they are found to attack the leaves of the plants.